BRONKHOPNEUMONIA AS COMORBIDITIES OF CMV INFECTION : STUDY CASE ON 1 YEAR 9 MONTHS OLD BOY - Wulan Widiasmaran; Ayu Anggraini Kusumaningrum; Fitri Amalia; Dimas Tri Anantyo (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background. Pneumonia is an acute lung parenchyma inflammation, which includes the alveoli and tissues. According to RISKESDAS 2018, pneumonia prevalence of children under five years old in Indonesia has increased from 1.6% in 2013 to 2% in 2018. Cytomegalovirus infection (CMV) is the most common congenital infection and causes high morbidity in newborns. The purpose of this case is to report a case in Semarang and conduct a discussion of pneumonia cases and a history of CMV infection so that proper treatment can immediately start.Method. Anamnesis carried out on February 1, 2020, at Government Hospital in Semarang. Data obtained from allonamnesis with the patient's mother, physical examination, supporting examinations, and medical records of patients. Case. Patient of a boy aged one year nine months that come to the ER with a chief complaint of fever and cough.Discussion. A boy aged one year nine months with fever and cough complaints about five days before entering the hospital. Sputum culture examination revealed the presence of Klebsiella pneumonia, then treated with cefoperazone sulbactam. The patient had a history of cytomegalovirus infection but not optimally treated because of the high avidity value.Conclusion. Patient has diagnosed with bronchopneumonia et causa Klebsiella pneumonia.